Pola Pendidikan Islam dalam Upaya Menurunkan Angka Penyebaran HIV/AIDS pada Remaja di Indonesia - Dimas Rayhan Giffary; Tegar Aditya Darma; Ridho Naufal Manaf (Journal of Creative Student Research, 2023)
Education is the most essential thing for a nation because the progress or backwardness of a nation is reflected in the level of education of its citizens. One form of education that functions innovatively and creatively towards its followers is Islamic education. Islamic education is derived from the Quran and the Sunnah and shapes a complete human being, one who believes in and is conscious of Allah (SWT). Education forms the basis for how an individual behaves towards others and their environment. The positive values in Islamic education can serve as a guide and foundation for the teenagers in Indonesia in their general conduct.